Is food insecurity more severe in South Asia or Sub-Saharan Africa?: A comparative analysis using household expenditure survey data - Smith, Lisa C.; Wiesmann, Doris (International Food Policy Research Institute, 2007)
This paper uses data from national household expenditure surveys to explore whether food insecurity is more severe in South Asia or Sub-Saharan Africa. It employs two indicators of the diet quantity dimension of food insecurity, or the inability to access sufficient food: the prevalence of food energy deficiency and the prevalence of severe food energy deficiency. It also employs two indicators of the diet quality dimension, indicating lack of access to nutritious food: the prevalence of low diet diversity and the percent of energy from staple foods. It finds the regions’ food energy deficiency prevalences to be quite close (51 percent in South Asia, 57 percent in Sub-Saharan Africa). However, the prevalence of severe food energy deficiency, which is more life threatening, is higher in Sub-Saharan Africa (51 percent versus 35 percent in South Asia). From a diet quality standpoint, the regions appear to suffer from a comparable and high reliance on staple foods in the diet to the neglect of foods rich in protein and micronutrients, but that Sub-Saharan Africa may be doing worse, as reflected in less diverse diets. The results confirm that both regions suffer from deep food insecurity problems but point to Sub-Saharan Africa as the region with the more severe problem, particularly when it comes to the diet quantity dimension of food insecurity. In deciding which region should be given greater emphasis in the international allocation of scarce development resources, the fact that the numbers of people affected by food insecurity are higher in South Asia should be taken into consideration.